THE ROLE OF AN UNDERSTANDING OF EDUCATIONAL PHILOSOPHY IN DEVELOPING A LOCAL CONTENT CURRICULUM (CASE STUDY AT PGRI 6 DENPASAR VOCATIONAL SCHOOL) - Herawan, Kadek Dedy (JURNAL EDUSCIENCE, 2024)
Lack of understanding of the principles of curriculum development means that educational institutions simply imitate without carrying out analysis and adjustments in the process of developing their curriculum. So we can be sure that educational goals will not be achieved optimally. One of the important things to understand in curriculum development is educational philosophy. Educational problems often arise and become a factor that can hinder the achievement of educational goals, but by understanding what educational philosophy is as a whole, you will be able to direct educational stakeholders to find out the source of the problem, the solutions offered, and steps in realizing the achievement of educational goals in the future, along with changing times, science, and technology. The local content curriculum is expected to be able to bridge the conditions of educational units in the regions with the achievement of national education goals, which is the hope of all Indonesian citizens who want equal distribution of human resources throughout Indonesia. The preparation and development of local content curricula is oriented towards various philosophical schools, which are then translated into philosophical foundations in the curriculum. These currents include perennialism, essentialism, existentialism, progressivism, reconstructionism, and post-modernism.